"Moskva‐Berlin, Berlin‐Moskau, 1900–1950": Memory and Forgetting. Issue 4 (3rd September 2021) - BULGAKOWA, OKSANA
Abstract : This article reconstructs and reexamines the dramatic events leading up to the "Moscow‐Berlin, 1900–1950" exhibition, jointly staged by the Berlinische Galerei and the Pushkin Museum of Fine Arts in 1995–96. Modeled upon the landmark "Moscow‐Paris" exhibit that had taken place at the Pompidou Center in 1979 and the Pushkin Museum in 1981, "Moscow‐Berlin" has been largely forgotten by time, despite the fact that it, too, was intially viewed as a blockbusters event. Beyond changing professional and cultural conventions, a series of underlying factors help to explain the contrasting reactions to the two exhibits: international politics and the art market, passing trends, and media discourses. By the time "Moscow‐Berlin" opened, interest in the Russian avant‐garde had faded, while interest in 1930s art and culture was on the rise, fueled not by commercial but by an ideological demand to reconceptualize the canon for writing history and art history. Additionally, "Moscow‐Berlin" was conceived of as a political event, not only vis à vis the art on display, but its very location: West Berlin. But during the early stages of planning and preparation, however, both the Soviet Union and the German Democratic Republic disappeared from the map: this solved some thorny political issues surrounding the exhibit, but it created myriad other problems. At first, German politicians hoped the exhibit would facilitate the return of trophy art taken from Germany at the end of the Second World War. When reality dispelled this illusion, the German press launched an extended campaign against the exhibitions, which would later impact how it was remembered. Meantime, of course, when the exhibit arrived in Moscow it opened in a city in the throes of socioeconomic unrest and a contentious presidential election. The display of Stalinist art in all its radiant glory sparked in some viewers nostalgia for the Soviet past, and partially suppressed the question of whether shame should accompany the art of Stalinism. Collective memory hoped instead to glide over the more painful chapters of the recent past.